Citation score normalized by cited references (CSNCR): The introduction of a new citation impact indicator. Issue 3 (August 2016) - Bornmann, Lutz; Haunschild, Robin
Highlights: A new field-normalized indicator is introduced, which is rooted in early insights in bibliometrics. The new indicator is defined as follows: the citation count of a focal paper is divided by the mean number of cited references in a field. The new indicator is called citation score normalized by cited references (CSNCR). Abstract: In this paper, a new field-normalized indicator is introduced, which is rooted in early insights in bibliometrics, and is compared with several established field-normalized indicators (e.g. the mean normalized citation score, MNCS, and indicators based on percentile approaches).Garfield (1979) emphasizes that bare citation counts from different fields cannot be compared for evaluative purposes, because the "citation potential" can vary significantly between the fields.Garfield (1979) suggests that "the most accurate measure of citation potential is the average number of references per paper published in a given field." Based on this suggestion, the new indicator is basically defined as follows: the citation count of a focal paper is divided by the mean number of cited references in a field to normalize citations. The new indicator is called citation score normalized by cited references (CSNCR). The theoretical analysis of the CSNCR shows that it has the properties of consistency and homogeneous normalization. The close relation of the new indicator to the MNCS is discussed. The empirical comparison of the CSNCR with other field-normalized indicators shows that it is slightly poorer able to field-normalize citation counts than other cited-side normalized indicators (e.g. the MNCS), but its results are favorable compared to two citing-side indicator variants (SNCS indicators). Taken as a whole, the results of this study confirm the ability of established indicators to field-normalize citations.